PERBANDINGAN RANGKA JEMBATAN TIPE WARREN DAN TIPE PRATT PADA JEMBATAN BRANTAS - Adi Nugroho Santoso; Sumaidi Sumaidi (Program Studi Teknik Lingkungan, Universitas Pembangunan Nasional Veteran Jawa Timur, 2021)
A bridge is a connecting facility for an area that functions as a supporting facility for the economy of the region. Bridges have a crucial function in an area to carry out activities and daily work such as trade, social, political and so on. In East Java, the type of truss used mostly uses Warren type trusses, so a comparison analysis with other types of bridges is needed to determine the most efficient type of bridge. In this analysis the Pratt type bridge is used. This analysis aims to compare the ratio of strength to total structure weight. From the output analysis, it is that the Warren type bridge the ratio of the structure is 3,417, while the Pratt type bridge has a ratio of strength to weight of the structure is 3,358. The deflection that occurs in the Warren truss structure is -0.0528 smaller than the Pratt type bridge which is -0.0571. The weight of the Warren type bridge structure weighs 18042.4 kg, while the Pratt type bridge is 19023 kg. Based on the analysis results obtained, it is shown that the ratio of the strength and weight of the Warren type bridge structure is 3,417 and the Pratt type is 3,358.